In vitro evaluation of Ultraviolet Radiation (UVR) exposure of the Retinal Pigmented Epithelium (RPE) and its relevance to Age-Related Macular Degeneration (AMD) - Anderson, Graham (The University of Edinburgh, 2021)
BACKGROUND: Age-related macular degeneration (AMD) is a degenerative disease of the retina and is a leading cause of legal blindness in the UK, effecting around 200 million individuals globally in 2020. The role of ultraviolet radiation (UVR) exposure in the pathology of AMD has been debated for decades with epidemiological evidence failing to find a clear consensus for or against it playing a role. A key reason for this is a lack of foundational research into the response of living retinal tissue to UVR in regard to AMD-specific parameters of tissue function. To this end, we sought to explore the response of cultured retinal pigmented epithelium (RPE), the loss of which heralds advanced AMD, to specific wavelengths of UVR across the UV-B and UV-A bands. METHODS: Using a custom built in vitro UVR exposure apparatus coupled with bandpass filters we exposed the immortalised RPE cell line, aRPE-19, to 10nm bands of UVR between 290 and 405nm. To assess physical cell dynamics during exposure, cells were cultured upon specialist electrode culture plates (ECIS®, Applied Biophysics) which allow for electrostatic interrogation of key cell parameters, such as well coverage and tight-junction integrity, in a non-invasive fashion. Following from this, UVR exposures were repeated and a rapid cell viability assay (PrestoBlue™, Thermofisher) was utilised to quantify wavelength-specific toxicity. Finally, a cellpaint-like high content imaging assay was developed in order to, at once, quantify intracellular oxidative stress, nuclear morphology, mitochondrial stress, epithelial integrity and cell viability as part of a cellprofiling approach to quantifying UVR toxicity. RESULTS: Electrostatic assessment of UVR-RPE indicated UV-A toxicity, beginning at 350nm, and recounted previously demonstrated UV-B toxicity. Cell viability analysis also highlighted increased toxicity at 350nm as well as 380nm. 350nm toxicity was further substantiated upon high content image analysis which highlighted increased mitochondrial dysfunction and oxidative stress at 350nm. CONCLUSION: aRPE-19 exhibit unique sensitivity to UV-A radiation, specifically at 350nm and 380nm. If upheld, such sensitivity will have an impact upon AMD geospatial risk scoring.
Keywords: age-related Macular Degeneration; AMD; ultraviolet radiation exposure; retinal damage; RPE cell; retinal pigmented epithelium cell; UVR toxicity